Vecinas y ciudadanas: las mujeres del Distrito del Sur y el uso de la voz “ciudadana” durante la república temprana (Dossier: El momento colombiano de las repúblicas andinas. Historia política) - Sevilla Naranjo, Rosita Alexandra (2021)
This article focuses on the term “woman citizen” during the Gran Colombia period. On the basis of theoretical assumptions from the history of ideas, it examines why said term appears in legal documents and personal correspondence of that time to refer to women of diverse social and economic status, although in the Constitution in force at the time and in government citizenship did not include women.